2016
DOI: 10.18632/oncotarget.7257
|View full text |Cite
|
Sign up to set email alerts
|

The status of epidermal growth factor receptor in borderline ovarian tumours

Abstract: The majority of borderline ovarian tumours (BOTs) behave in a benign fashion, but some may show aggressive behavior. The reason behind this has not been elucidated. The epidermal growth factor receptor (EGFR) is known to contribute to cell survival signals as well as metastatic potential of some tumours. EGFR expression and gene status have not been thoroughly investigated in BOTs as it has in ovarian carcinomas. In this study we explore protein expression as well as gene mutations and amplifications of EGFR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
2
6
0
1
Order By: Relevance
“…8,9 Our study comprised of maximum number of cases of serous histotype (48.49%). This was similar to other studies conducted by Showeil et al, Asadinejad et al, Onwuka, Nielsen et al, Sapna Goel et al, and Cirstea et al [8][9][10][11][12][13] High grade tumors constituted maximum number of cases in the present study, comprising of 19 cases (57.57%). Our findings were similar to study conducted by Nielsen et al, in which 45% tumors were poorly differentiated followed by 30% well differentiated tumors and 25% moderately differentiated tumors with a significant p value of<0.001.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…8,9 Our study comprised of maximum number of cases of serous histotype (48.49%). This was similar to other studies conducted by Showeil et al, Asadinejad et al, Onwuka, Nielsen et al, Sapna Goel et al, and Cirstea et al [8][9][10][11][12][13] High grade tumors constituted maximum number of cases in the present study, comprising of 19 cases (57.57%). Our findings were similar to study conducted by Nielsen et al, in which 45% tumors were poorly differentiated followed by 30% well differentiated tumors and 25% moderately differentiated tumors with a significant p value of<0.001.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies conducted by Asadinejad et al showed similar results (p value=0.567). 11 Contradicting results were found in studies conducted by Cirstea et al, Showeil et al, Goel et al and Nielsen et al [8][9][10]13 These studies demonstrated that there was significant association between different grades of ovarian epithelial tumors and HER-2 expression. This difference was due to larger study sample taken into account by them and differences in race, age and population of study.…”
Section: Discussionmentioning
confidence: 96%
“…EGFR mutations are a rarity in SBTs and have not been previously reported in LGSOC. Showeil et al found a higher nuclear and cytoplasmic staining of EGFR in 61 SBTs and 10 LGSOC tumors compared to benign ovarian tumors or HGSOC tumors but could not detect any mutation [31]. Activating EGFR mutation can upregulate the PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The signaling pathway for EGFR is mediated by ligands including the epidermal growth factor in the regulation of cell proliferation, differentiation and apoptosis in normal cells. Research into the mechanisms of EGFR overexpression has focused on mutations and amplifications in the coding region of the gene containing the receptor tyrosine kinase domain . However, few studies on SNP variants in this region have been linked to EOC or other ovarian cancer histologic subtypes .…”
Section: Discussionmentioning
confidence: 99%
“…63 However, few studies on SNP variants in this region have been linked to EOC or other ovarian cancer histologic subtypes. 61,63 EGFR SNP rs114972508 is located in intron 1 of the EGFR gene. The location of the SNP is approximately 70 kb upstream of a VDR binding site also within EGFR intron 1 that has been shown experimentally to down regulate EGFR expression and proliferative function.…”
Section: Snp Id (Effect/other Allele) Nearest Gene(s)mentioning
confidence: 99%